2016
DOI: 10.1155/2016/8740264
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Optic Neuritis: A Rare Complication after Measles-Mumps-Rubella Vaccination in a 30-Year-Old Woman

Abstract: Purpose. To report a case of unilateral optic neuritis following Measles-Mumps-Rubella (MMR) vaccination. Methods. A 30-year-old female developed unilateral optic neuritis five days after a Measles-Mumps-Rubella (MMR) booster vaccination. The patient displayed unilateral involvement, with severe visual loss. However, visual acuity improved significantly after four days of intravenous steroid therapy with 500 mg/day of methylprednisolone. Conclusions. Optic neuritis is one of the rare complications associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Therefore, MMR vaccine administration is imperative. However, several cases of optic neuritis were observed following the MMR vaccine, thought to be associated with the toxic reactivation of the non-viral component of the vaccine (De Giacinto et al, 2016;Riikonen, 1989). All but one case subsequently developed MS (Riikonen, 1989).…”
Section: Measles Mumps and Rubella Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MMR vaccine administration is imperative. However, several cases of optic neuritis were observed following the MMR vaccine, thought to be associated with the toxic reactivation of the non-viral component of the vaccine (De Giacinto et al, 2016;Riikonen, 1989). All but one case subsequently developed MS (Riikonen, 1989).…”
Section: Measles Mumps and Rubella Vaccinementioning
confidence: 99%
“…Of note, MS can develop 7-10 years after an acute demyelinating attack and thus, there may be limited use of the aforementioned studies. (De Giacinto et al, 2016;Riikonen, 1989;Joyce and Rees, 1995;Lim et al, 2004) Nonetheless, several studies have since aimed to understand if there is an association with the MMR vaccine and the development of MS and all but one have returned negative (DeStefano et al, 2003;Zorzon et al, 2003;Ramagopalan et al, 2009;C Ahlgren et al, 2009;C Ahlgren et al, 2009;MF Farez and Correale, 2011) The singular study that did find an association had a relatively small sample size, however (Zorzon et al, 2003).…”
Section: Measles Mumps and Rubella Vaccinementioning
confidence: 99%
“…Other studies have reported similar neuro-ophthalmologic complications following other COVID-19 vaccines Ad26.COV2.S vaccine (Janssen Pharmaceutical Companies) [6], Pfizer-BioNTech vaccine, AstraZeneca-Oxford vaccine [7], Covishield vaccine [8], and Sinopharm vaccine [9]. Similar neuroophthalmologic complications have been reported following the administration of the measles vaccine [10,11].…”
Section: Discussionmentioning
confidence: 58%
“…Of special interest, there were several cases of ON following days to weeks of the MMR vaccine administration [ 100 ]. All except one case, in a 13-year-old patient [ 101 ], showed significant improvement following treatment and did not develop clinically definite MS.…”
Section: Vaccination Overview In the Context Of Multiple Sclerosismentioning
confidence: 99%